Persepsi Pelaku Usaha Mikro, Kecil dan Menengah (UMKM) Terhadap Insentif Perpajakan Selama Pandemi Covid-19 - Leonardo Zulkarnain; Zulfa Devina Rahman (Juara: Jurnal Riset Akuntansi, 2023)
The background of this research is related to tax incentives offered by the Indonesian tax authority especially during Covid-19 pandemic. According to The Central Bank of Indonesia, the small and middle-sized enterprises (SMEs) were among the hardest hit during the pandemic. This research aims at exploring the perceptions of SMEs, mainly in the South of Jakarta, towards tax incentives and investigating whether such incentives were optimized by SMEs and able to help alleviate their tax burden. This study used Responsive Regulation Theory to discern whether tax incentive policy benefitted SMEs and was introduced in accordance with the need of SME taxpayers. This research used qualitative approach by using semi-structured interviews to collect data from SMEs. There were thirteen SMEs participating in this research with the majority registered in the tax system. Results indicate that around sixty percent of participants did not have information in relation to tax incentives. Meanwhile, all participants stated that tax incentives, including tax cut and tax amnesty, are highly important for them. Apparently, a lack of information prevented these taxpayers from utilizing such incentives. Therefore, future tax information may need to be disseminated more comprehensively to reach a wide array of taxpayers, especially SMEs.